Legal Protection For Indonesian Fishery Products In Facing Environmental Protection In International Trade - Widyastuti, Tiyas Vika (Diktum: Jurnal Ilmu Hukum, 2022)
International trade principally aims to exploit the market, thus traditionally speaking, have a little concern about protecting the environment. Only after entering this new era of international trade, the Indonesian government then finds the challenge in controlling the trade’s speed and market since the everything is regulated under a specific international trade regulation that is not entirely concern with protecting national interests. Many Indonesian popular products could not compete internationally, since they tend to fail in fulfilling the international standards of exported goods. This will inevitably hinder the national economy, more specifically in gaining foreign investments. One example of the challenges posed by regulation that interfere with the economic growth in the context of international trade is the way environment regulation dampens the effort to export the Indonesian fishery products. The primary problem is that even though Indonesian domestic regulation has put some sort of legal protection for Indonesian fishery products, they still fail to fulfil the environmental standard set by some export-destination countries, such as the USA and the European. Against this backdrop, this research aims to analyze the application of domestic regulation on fishery in Indonesia. We are using the socio-legal approach to understand the way the domestic regulation has failed to fulfill its legal aim, which is to implement the act of law related to fishery, environment, and quality standards to fit the market’s demand, as well as to improve the environment surrounding the fishery industry according to the Code of Conduct for Responsible Fisheries. Based on primary and secondary data from observations and interviews, we contend that there are at least three issues surrounding the failure: 1. The problem regarding the substance of the regulation itself, 2. The disorganized authority within the institutional structure, and 3. The legal culture surrounding the people involved as resulted from their beliefs and personal economic consideration